2000
DOI: 10.1097/00007691-200010000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Pharmacokinetics and Bayesian Estimation in Pediatric Patients

Abstract: The vancomycin pharmacokinetic profile was characterized in six pediatric patients and the potential of nonlinear mixed effects modeling and Bayesian forecasting for vancomycin monitoring was explored using NONMEM V (1.1). Based on steady state serial vancomycin concentrations, the estimates of mean t1/2, Vd, and Cl derived by the Sawchuk and Zaske method (1) were 3.52 hours, 0.57 L/kg, and 0.12 L/h per kg, respectively. NONMEM analysis demonstrated that a weight-adjusted two-compartment model described indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
5
29
0
4
Order By: Relevance
“…Wrishko et al also evaluated the predictive performance of VCM concentration in pediatric patients and showed that trough sampling alone could provide clinically acceptable predictions of VCM concentrations at other sam- pling points. 34) They also showed that a later sampling point improved the relative accuracy and precision of trough prediction. Theseˆndings coincide with our present results, although the compartment model used in each study is diŠerent.…”
Section: Resultsmentioning
confidence: 98%
“…Wrishko et al also evaluated the predictive performance of VCM concentration in pediatric patients and showed that trough sampling alone could provide clinically acceptable predictions of VCM concentrations at other sam- pling points. 34) They also showed that a later sampling point improved the relative accuracy and precision of trough prediction. Theseˆndings coincide with our present results, although the compartment model used in each study is diŠerent.…”
Section: Resultsmentioning
confidence: 98%
“…In children, the standard dose evaluation studies of antimicrobials are usually based on a "nonselected" pediatric population and do not take into account the potential impact of the disease and disease state, which are the main factors that ultimately influence drug exposure in the clinical setting (17). For the purposes of comparison, the demographics and pharmacokinetic parameters of vancomycin obtained from different pediatric studies (10,18,19) are summarized in Table 4. The magnitude of the differences provides strong argument for studying pharmacokinetics in selected subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this same study a weighted average of vancomycin CL from the three reported age groups (mean age of groups 3.9, 5.6, and 7.6 years) was calculated to obtain an overall mean vancomycin CL in children. The mean vancomycin CL for each study was: 0.114(15), 0.103(16), 0.157(17) and 0.110 L/hr/kg(18) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies were identified in which vancomycin CL was calculated based on direct measures of vancomycin levels in children(15-18). In one study(17) a recalculated vancomycin CL was required to account for vancomycin infusion time (19), which had not been taken into account by the authors.…”
Section: Methodsmentioning
confidence: 99%